Preparation and Photocatalytic Performance of Nano-TiO2/γ-Al2O3 Composites - Qu, Hua (Asian Journal of Chemistry, 2013)
Nano-TiO2/g-Al2O3 composites were prepared by sol-gel method when the g-Al2O3 was employed as support. The structure, surface information and specific surface area of composites were characterized by X-ray diffraction, scanning electron microscopy and N2 adsorption. The photocatalytic performance of composites were appraised using phenol solution as the model pollutant. The result indicated that TiO2 was successfully loaded on the surface of g-Al2O3 and the particle size of TiO2 increased with the increase of calcination temperature. Influence of calcination temperature, dosage of the composite on the photocatalytic performance were investigated. When the dosage of composites which were calcined at 500 ºC was 3 g/L, we found that the degradation rate of phenol solution reached the maximum 45.6 %. After three cycles, the degradation rate of phenol solution decreased about 25 %.